Perceptions of Artificial Intelligence use among chemistry students at Universidad Estatal a Distancia: a diagnostic study - Rodríguez-Zúñiga, Ana L. (2026)
This diagnostic study aimed to identify and interpret how chemistry students at the Chair of Chemical Sciences for Engineering of the State Distance University (UNED) are using generative AI in their academic activities, and whether their perceptions changed after receiving guidance on its ethical and academic use. A mixed-methods approach was employed, incorporating data collection through an opinion survey of 82 students before and after training focused on the ethical use of tools such as Semantic Scholar, ChatGPT, Copilot, and DeepSeek. Data were analyzed using descriptive statistics and the Student’s t-test, considering differences between both time points. The results showed that, although attitudes toward AI remained positive, no statistically significant changes were observed after receiving the training. The study concludes that ethical literacy in AI should be incorporated across higher education, accompanied by teacher guidance and sustained practice.